Educating children on sexual matters based on the teaching of Islam: the role of Muslim parents - Ahmad Sudan, Salmi (Center for Promoting Ideas, 2015)
The increasing permissiveness towards premarital sexual activities among Malay Muslim teens in Malaysia whose culture and religion (Islam) strongly oppose sexual activities outside marriage is indeed worrying. This scenario may possibly indicate that Muslim children are not getting the appropriate education and guidance in matters pertaining to sexuality amidst living in an era in which exposure to sexual content that encourages free expression of sexuality is high particularly through the widespread access to the internet at young age. Sexuality is a taboo subject in Muslim homes and many Muslim parents are not ready to discuss sexual issues with their children due to embarrassment, feeling of uneasy, and have lack of knowledge to do so (Nurullah et al, 2010, Jahanfar S et al, 2009). This paper discusses sexuality concerns faced by young Muslim adolescents at present with the focus on the responsibility of Muslim parents in educating their children on sexual matters based on the teaching of Islam. This paper asserts that Muslim parents should take the lead in educating their children on sexual matters using the guiding principle of the Quran and sunnah to protect their children against undesirable sexual behaviors that bring disastrous consequences such as unwanted pregnancies, killing of babies, and sexual transmitted diseases. parents